THE IMPORTANCE OF TEACHING PUBLIC RELATIONS - Jonida PETRO (Association of Social and Educational Innovation, 2023)
This article focuses on Public Relations as a profession and how the education system is part of effectively teaching public relations' programs in universities. It opens with an introduction to the origins of public relations, its evolution and what the future holds for PR professionals. Furthermore, it outlines the principles, knowledge and skills required by those who, after completing their studies, will become PR practitioners exploring specific career paths and scenarios. This article, as well, touches on issues such as teaching ethics in public relations, communication as a key aspect in succeeding in PR, as well as the distinction between marketing and advertising versus Public Relations. Finally, the article emphasizes that professionals without the relevant education in public relations usually fall into the category of journalists or communication agents, unless they are able to pursue continuing education in this area.